Polarization and US foreign policy: when politics crosses the water's edge - Friedrichs, Gordon; Tama, Jordan (Springer Nature Switzerland, 2024)
Chapter 1. Introduction: Polarization and America’s Role in the World” -- 2. Chapter 2. Are We Drowning at the Water’s Edge? Foreign Policy Polarization among the US Public -- Chapter 3. Finding the Water’s Edge: When Negative Partisanship Influences Foreign Policy Attitudes -- Chapter 4. Beyond Party: Ideological Convictions and Foreign Policy Conflicts in the US Congress -- Chapter 5. Foreign Policy Free Agents: How Lawmakers and Coalitions on the Political Margins Help Set Boundaries for U.S. Foreign Policy -- Chapter 6. Bryan W. Marshall and Patrick J. Haney, “Support and Defend? Executive Ascendancy and Congressional Abdication in US Foreign Policy -- Chapter 7. James Bryan and Jordan Tama, “The Prevalence of Bipartisanship in U.S. Foreign Policy: An Analysis of Important Congressional Votes -- Chapter 8. Congressional Polarization and Limitation Riders in Foreign Aid Appropriations -- Chapter 9. Social Fabric Decay: The Case of Congressional Travels Abroad. Chapter 10. Brakeman or Booster? Presidents, Ideological Polarization, Reciprocity and the Politics of US Arms Control Policy -- Chapter 11. Polarized We Trade? Intra-Party Polarization and U.S. Trade Policy -- Chapter 12. Polarization, Casualty Sensitivity, and Military Operations: Evidence from a Survey Experiment -- Chapter 13. The Reputational Consequences of Polarization for American Foreign Policy: Evidence from the US-UK Bilateral Relationship -- Chapter 14. Looking Ahead: Prospects for Effective Foreign Policy and Avenues for Further Research.